Geological Mapping and Multi-Electrode Resistivity Survey for Potential Groundwater Exploration in Ayer Lanas Village and Its Surroundings, Jeli District, Kelantan, Malaysia - Dony Adriansyah Nazaruddin (Science Faculty of Chiang Mai University, 2020)
Geological mapping and multi-electrode resistivity survey were carried out in Ayer Lanas village and its vicinity, in Jeli district, Kelantan, Malaysia as part of the groundwater resources exploration for rural water supply. Geological mapping in the study area has shown that the area is composed of granitic rocks (megacrysticbiotite granite porphyry) overlain by Quaternary alluvial deposits and the weathered granite. The Schlumberger array with a maximum electrode spread of 200 m was conducted by employing three resistivity survey lines, where data were collected by using ABEM Terrameter SAS 4000 and ABEM LUND ES464 electrode selector system, and processed by using RES2DINV software. The images were presented in the form of two-dimensional (2D) resistivity profiles providing a clear view of the distribution of granitic rock basement, alluvial deposits and the weathered granite as well as potential groundwater zones. The results show that the study area has potential groundwater resources existing in the alluvium and the weathered granite, which become the unconfined aquifers. This combination of geological mapping and multi-electrode resistivity survey is a reliable and successful approach to identifying potentially favorable zones for obtaining groundwater in the study area.